How Health Impact Assessments (HIAs) Help Us to Select the Public Health Policies Most Likely to Maximise Health Gain, on the Basis of Best Public Health Science - Dreaves Hilary A (AIMS Press, 2016)
Health Impact Assessment (HIA) is a decision support tool intended to present timely, evidence-based recommendations to decision makers in all sections of society in order to accentuate potential positive health and well-being impacts (and mitigate potential negative impacts) of policies, plans (including local and neighbourhood plans), programmes and projects (including infrastructure and local development proposals), in order to reduce health inequalities/disparities. HIA is a well established and proven means of linking research evidence from public health and the environmental sciences with equitable decision making processes at all levels, from local to global. It may also provide a platform for examination of research proposals to strengthen the impact statement therein, identifying potential for future public benefit. This paper highlights some of the main drivers for a timely re-emphasis on the use of best scientific evidence and systematic HIA to inform decision making for future public benefit, citing the example of air pollution.